PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN (STUDI PADA LAPANGAN FUTSAL HIDAYAT FUTSAL SQUARE) - ROCHMAT HIDAYAT HARIYONO (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This study aims to examine the effect of Product Quality, Service Quality, and Price Perception on Customer Satisfaction. The number of samples in this study were 100 futsal Hidayat Futsal Square customers. Analysis of the data used is multiple linear regression analysis. The results of this study conclude that the results of partial testing of Product Quality have a significant effect on customer satisfaction, Service Quality has a significant effect on customer satisfaction, and Price Perception has a significant effect on customer satisfaction